Singularity and Community: Levinas and democracy. Issue 4 (20th March 2016) - Zhao, Guoping
Abstract: This article explores and extends Levinas's ideas of singularity and community as multiplicity and argues that his identification of language and discourse as the means to create ethical communities provides tangible possibilities for rebuilding genuine democracy in a humane world. These ideas help us reimagine school and classroom as communities open to differences. They also give education the opportunity to support the emergence of the singular and the irreducible—infinite human beings.